ANTASEDEN CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSETS PADA PERUSAHAAN PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dody Firman; Zandra Zandra (Fisarrearch, 2022)
This study aims to determine whether there is an effect of the Current Ratio and Debt to Equity Ratio partially or simultaneously on Return On Assets. The research approach uses an associative approach. The sampling criteria used purposive sampling technique, namely the determination of samples with certain criteria, so that of the seven companies that became the population there were only five companies that could be sampled in the Cosmetics and Household Goods sub-sector companies listed on the Indonesia Stock Exchange. Data collection techniques using documentation studies. The data analysis technique used multiple linear regression, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), hypothesis testing (t test and F test) and coefficient of determination (r-square). Data processing in this study using SPSS (Statistical Product and Service Solution) 23 for Windows. The results of the study prove that partially Current Ratio has a significant effect on Return On Assets and Debt to Equity Ratio has a significant effect on Return On Assets. Then simultaneously Current Ratio and Debt to Equity Ratio have a significant effect on Return On Assets.